PENGARUH PENDIDIKAN KEWIRAUSAHAAN DAN EFIKASI DIRI TERHADAP MINAT BERWIRAUSAHA MAHASISWA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU - Gita, Gita Aulya Anggraini; Sumarno; M.Yogi Riyantama Isjoni (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This research aims to determine the influence of entrepreneurship education and self efficacy on the entrepreneurial interest of FKIP Riau University students. The population in this study were 1351 active FKIP class of 2020 students and a sample of 93 students. The sampling technique uses a random sampling method. This research uses primary data obtained by distributing questionnaires. The data analysis technique uses multiple linear regression analysis. Based on the research results, it shows that entrepreneurship education and self-efficacy influence students' entrepreneurial interest, this is shown through the t test with the results of the entrepreneurship education variable value being 0.001 < 0.05 and the self-efficacy variable value being 0.014 < 0.05. Entrepreneurship education has a positive and significant effect, meaning that if students have good entrepreneurship education it will increase their interest in entrepreneurship. Self-efficacy has a positive and significant effect, meaning that if students have high self-efficacy it will increase their interest in entrepreneurship. Likewise, if students have low entrepreneurial education and low self-efficacy, their level of interest in entrepreneurship will also be low.